Health effects of exposure to isocyanates in a car factory - Klusáčková, Pavlína; Dušková, Šárka; Mráz, Jaroslav; Navrátil, Tomáš; Vlčková, Štěpánka; Pelclová, Daniela (Central European journal of public health, 2022)
OBJECTIVES: Isocyanates are known to induce occupational diseases. The aim of this work was to assess the health effects of exposure to isocyanates and to test the sensitivity of selected parameters for early detection of isocyanate-related allergic diseases. METHODS: In total, 35 employees from one factory were tested: 26 workers exposed to isocyanates (exposed group) and nine office workers (control group). All subjects filled in a questionnaire regarding possible health problems. Fractional exhaled nitric oxide (FeNO) and spirometry were measured for each subject at the same time during two consecutive working days. A urine sample was taken for a biological exposure test (BET). RESULTS: No significant difference was found between the exposed and control groups for spirometry parameters and FeNO. However, in the exposed group, FeNO was highly elevated (> 50 ppb) in five subjects (all reporting health problems at the workplace, all with normal spirometry and non-smokers). The BET revealed a significant difference (p < 0.001) between the exposed and control groups for 4,4´-methylenediphenyl diamine (MDA) in the urine. CONCLUSIONS: Our examination showed the usefulness of the BET in monitoring of workplace exposure to isocyanates and the importance of FeNO in monitoring of allergic inflammation of airways in non-smoking employees with normal spirometry.
Keywords: nemoci z povolání; automobily; fractional exhaled nitric oxide; biological exposure test; Automobiles; isokyanatany; Humans; Occupational Exposure; isocyanates; occupational asthma; pracovní expozice; Isocyanates; Workplace; pracoviště; methylene diphenyl diisocyanate; lidé; Occupational Diseases